Decrease in HBsAg After TAF Switching from Entecavir During Long-Term Treatment of Chronic Hepatitis B Virus Infection - Kazuto Tajiri; Yuka Hayashi; Aiko Murayama; Nozomu Muraishi; Masami Minemura; Ichiro Yasuda (Viruses)
Achieving HBsAg seroclearance is a key goal in treating chronic hepatitis B virus (HBV) infection but remains difficult with nucleos(t)ide analogues (NAs). Tenofovir alafenamide fumarate (TAF), a recommended NA for managing chronic HBV infection (CHB), has uncertain effects on HBsAg levels and potential adverse events when used long-term after switching from entecavir (ETV). We retrospectively evaluated 77 CHB patients, including 47 who switched from ETV to TAF with a median follow-up of 40 months post-switch and a median of 60 months of HBsAg monitoring pre-switch. No significant change in HBsAg levels was observed in the overall cohort post-switch, consistent with the ETV continuation group. However, a significant decrease in HBsAg was noted in patients with HBsAg < 100 IU/mL at the time of switching. HBsAg loss occurred in three patients who switched to TAF. No adverse effects were observed, and TAF was well tolerated. The most significant factor associated with achieving HBsAg < 100 IU/mL was the Fib-4 index, a marker of liver fibrosis, at the time of switching. Switching from ETV to TAF is an effective strategy in CHB management, with hepatic inflammation potentially playing an essential role in achieving HBsAg decrease. Patients with increased Fib-4 index were significantly more likely to show decreased HBsAg. This finding suggests patients with mild to moderate fibrosis may respond better to TAF in terms of HBsAg reduction.